ANALISIS TINGKAT PEREKONOMIAN DESA LOPO KECAMATAN BATUDAA PANTAI KABUPATEN GORONTALO. - Rezal I. Akuba; Harijono Imbran; Ramlah Alaktiri (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2025)
This study aims to determine the economic level of Lopo Village, Batudaa District, Gorontalo Regency. The study employed a qualitative approach using interviews. The data source relied on village profile data from 2023.The results indicate that Lopo Village relies heavily on marine economic potential, which is the primary source of livelihood for its residents. Other sources of income besides fisheries include corn and coconuts, which are found in the highlands, but whose productivity is still relatively low. The village's economic level remains relatively low, supported only by the fisheries sector, with a small portion coming from plantations. Consequently, economic growth remains slow, as evidenced by low purchasing power. The community faces significant obstacles due to the traditional nature of the fisheries sector.